Effect of Contact Time on Biosorption of Pb(II) Metal Ions Using Biosorbent from Durian Peel (Durio zibethinus L) - Esti Ramadhani; Desy Kurniawati; Fitri Amelia; Ananda Putra (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Lead metal (Pb2+) is a heavy metal that is dangerous and has high toxicity. Pb2+ metal comes from industrial waste such as electroplating, paint, and the textile industry so it can find air. An effective, efficient, and economical method to overcome air contact with the biosorption method. Pb2+ metal ion biosorption using durian peel (Durio zibethinus L) as biosorbent. The purpose of this study was to determine the optimal conditions for the absorption of Pb2+ metal ions using the batch method with variations in speed and stirring time. The results showed that the optimal condition for Pb2+ absorption occurred at a contact time of 60 minutes with an absorption capacity of 33.6163 mg/g.